Effect of shading screens on the production and quality of ‘Smooth Cayenne’ pineapple - de Araújo, Humberto Sampaio; Do Carmo, Silvia Antoniali; Dos Santos, Neli Cristina Belmiro; Freitas, Pâmela Gomes Nakada [UNESP]; Purquerio, Luis Felipe Villani (FapUNIFESP (SciELO), 2021)
In pineapple cultivation, it is common to cover the fruit with newspaper, in order to avoid scalding caused by sunburn. However, the scarcity of material and the large labor force required have led to the search of control alternatives. This study aimed to evaluate the use of shading screens in the production and quality of ‘Smooth Cayenne’ pineapple. A randomized blocks experimental design was used, with five treatments (fruits covered with newspaper and plants covered with screens with 35, 40, 50 and 80 % of shading), four replicates and two seasons (summer and winter). In the summer, the use of screens with 50 % of shading provided average gains of 22 and 39 % of total and commercial mass of crowned fruits per plant and gains of 22 and 40 % of total and commercial yield per hectare, respectively. The gradual increase in shading intensity resulted in a decrease in the qualitative attributes of the fruits, when compared to covering the fruits with newspaper. Screens with up to 50 % of shading can replace newspaper when covering the fruits to avoid scalding.
Efeito de telas de sombreamento na produção e qualidade de abacaxi ‘Smooth Cayenne’
Keywords: Ananas comosus (L.) Merril; Artificial shading; Protected cultivation